Screening for Urease-Producing Bacteria from Limestone Caves of Sarawak - Omoregie, Armstrong Ighodalo; Senian, Nurnajwani; Ye Li, Phua; Hei, Ngu Lock; Leong, Dominic Ong Ek; Henry Ginjom, Irine Runnie; Nissom, Peter Morin (Borneo Journal of Resource Science and Technology, 2016)
Urease is a key enzyme in the chemical reaction of microorganism and has been found to be associated with calcification, which is essential in microbially induced calcite precipitation (MICP) process. Three bacterial isolates (designated as LPB19, TSB31 and TSB12) were among twenty-eight bacteria that were isolated from samples collected from Sarawak limestone caves using the enrichment culture technique. Isolates LPB19, TSB31 and TSB12 were selected based on their quick urease production when compared to other isolates. Phenotypic characteristics indicate all three bacterial strains are gram-positive, rod-shaped, motile, catalase and oxidase positive. Urease activity of the bacterial isolates were measured through changes in conductivity in the absence of calcium ions. The bacterial isolates (LPB19, TSB12 and TSB31) showed urease activity of 16.14, 12.45 and 11.41 mM urea hydrolysed/min respectively. The current work suggested that these isolates serves as constitutive producers of urease, potentially useful in inducing calcite precipitates.